2017
DOI: 10.4081/aiua.2017.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patient with atypical leiomyoma of the bladder presenting as flank pain: A case report

Abstract: Atypical leiomyoma is a rare tumor of the bladder whose correct diagnosis with imaging techniques and cystoscopy is difficult. This tumor is prevalent in females and more common in middle age. In the present study we report a rare case of atypical leiomyoma presenting as flank pain and history of recurrent urinary tract infections in an elderly female. Ultrasound (US) showed that the wall of bladder was thickening and irregular, especially in the lower part of the bladder. US revealed hypoechoic solid mass wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Our case was asymptomatic except for microhematuria. However, since various symptoms, such as urinary retention, hematuria, and dyspareunia, are possible[ 4 , 7 - 12 ], a thorough history is necessary. In a review by Goluboff et al [ 4 ], 49% of the 37 patients presented with obstructive symptoms, 38% showed irritative symptoms, 11% had hematuria, and 19% were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our case was asymptomatic except for microhematuria. However, since various symptoms, such as urinary retention, hematuria, and dyspareunia, are possible[ 4 , 7 - 12 ], a thorough history is necessary. In a review by Goluboff et al [ 4 ], 49% of the 37 patients presented with obstructive symptoms, 38% showed irritative symptoms, 11% had hematuria, and 19% were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In a case report by Xin et al [ 10 ], a 44-year-old female with dyspareunia was diagnosed with bladder leiomyoma coexisting with uterine leiomyoma on histological examination. Saidi et al [ 11 ] reported leiomyoma of the urinary bladder presenting with hematuria, and Ameli et al [ 12 ] reported atypical leiomyoma of the bladder presenting as flank pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation